Fucosylated exosomal miRNAs as promising biomarkers for the diagnosis of early lung adenocarcinoma - Chen, Xiongfeng; Yu, Lili; Hao, Kun; Yin, Xiaoqing; Tu, Mingshu; Cai, Liqing; Zhang, Liangming; Pan, Xiaojie; Gao, Qi; Huang, Yi (Frontiers in Oncology, 2022)
Background: Considering the absence of apparent symptoms at early stage, most patients with lung adenocarcinoma (LUAD) present at advanced stage, leading to a dismal 5-year survival rate of <20%. Thus, finding perspective non-invasive biomarkers for early LUAD is very essential. Methods: We developed a fucose-captured strategy based on lentil lectin-magnetic beads to isolate fucosylated exosomes from serum. And then, a prospective study was conducted to define the diagnostic value of serum exosomal miRNAs for early LUAD. A total of 310 participants were enrolled, including 146 LUAD, 98 benign pulmonary nodules (BPNs) and 66 healthy controls (HCs). Firstly, exosome miRNAs in discovery cohort (n=24) were profiled by small RNA sequencing. secondly, twelve DEmiRs were picked for further screening in screening cohort (n=64) by qRT-PCR. finally, four candidate miRNAs were selected for further validation in validating cohort (n = 222). Results: This study demonstrated the feasibility of fucose-captured strategy for isolation of fucosylated exosomes from serum, evidented with exosomal characteristics identified by TEM, NTA and western blot, as well as rapid and convenient operation of <10 minutes. Furthermore, a miRNA panel for early LUAD comprised of miR4732-5p, miR451a, miR486-5p and miR139-3p was defined with an AUC of 0.8554 at 91.07% sensitivity and 66.36% specificity. Conclusions: Fucose-captured strategy provides a reliable, as well as rapid and convenient approach for isolation of tumor-derived exosomes from serum. A four-fucosylated exosomal miRNA panel presents good performance for early LUAD diagnosis.